Quality of Life of the Guguk Palembang Malay Community from the Perspective of Islamic Economics - Erdah Litriani; Maya Panorama; Mohammad Syawaludin (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Quality of life is commonly assessed through material indicators such as education and income; however, perceptions of well-being are also strongly influenced by cultural factors that remain underexplored, particularly in traditional urban communities. This study examines the influence of education, income, and culture on perceived quality of life within the Guguk Palembang Malay community from an Islamic economic perspective. A mixed-methods approach was employed, combining a quantitative survey of 500 respondents with qualitative in-depth interviews. The analysis explores the relationships between socio-economic variables, cultural dimensions, and quality-of-life perceptions. The findings indicate that education and income significantly affect material aspects of quality of life, including employment opportunities, income stability, and access to healthcare. Beyond material conditions, culture manifested in social cohesion, local traditions, and cultural identity plays a critical role in shaping perceptions of well-being. Individuals and communities with a stronger attachment to local cultural heritage report more positive evaluations of their quality of life. Additionally, age and social status contribute to variations in these perceptions. From an Islamic economic perspective, quality of life encompasses both material and non-material dimensions aligned with the principles of maqāṣid al-sharīʿah, including the protection of life, intellect, lineage, and wealth. The study underscores the importance of integrating cultural considerations into development policies alongside educational and economic improvements. To enhance quality of life in accordance with maqāṣid al-sharīʿah, policy efforts should focus on three key areas: integrating Islamic values into equitable education systems, promoting inclusive financial programs and fair employment, and preserving cultural heritage through education and culturally based economic initiatives. This culturally sensitive approach is essential for holistic development in traditional urban communities.